Impaired sports performance of athletes suffering from pollen-induced allergic rhinitis: a cross-sectional, observational survey in German athletes - Salem, L.; Dao, V. A.; Shah-Hosseini, K.; de Marees, M.; Mester, J.; Mösges, R.; Vent, J. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Allergic rhinitis has major impacts on sports performance of athletes. The present study aimed at determining the frequency of seasonal pollen allergy and analyzing the impacts of pollen allergy, the choice of allergy treatments and their benefits for sports performance in a group of professional and recreational athletes. METHODS: The study was conducted as a self-reported questionnaire survey. Subjects were recruited from the German Sport University and the Cologne Marathon 2014 during the peak pollen season of 2014. RESULTS: Athletes returned 636 completed questionnaires, 42.6% of participants reported suffering from a pollen allergy and 30.2% also suffered from asthma. Performance impairments were reported in more than 80% of allergic subjects. In all, 82.2% of subjects used symptomatic medications, 32.3% alternative therapies, and 47.6% allergen immunotherapy. Subjects who used immunotherapy had fewer impaired training bouts than those who used symptomatic and alternative therapies. The majority of subjects had concerns about allergy treatment such as side effects, negative impacts on sports performance and lack of long-term effects. CONCLUSIONS: This study confirmed a high prevalence of pollen allergy among German athletes. The majority of allergic rhinitis athletes were undertreated, and the reason could be their reservations about allergy treatments. Pollen allergy tremendously reduced sports performance of athletes during the pollen season. This impact can be lessened with proper treatment such as immunotherapy. Better understanding of available treatment modalities should be provided to patients and physicians to improve sports performance of athletes suffering from pollen allergy.